2021
DOI: 10.1108/lhs-11-2020-0094
|View full text |Cite
|
Sign up to set email alerts
|

Change starts with me: an impact evaluation of a multiprofessional leadership programme to support primary care networks in the South East of England

Abstract: PurposeThis paper aims to present the impact evaluation findings from a multiprofessional leadership programme commissioned in the South East of England to support primary care networks (PCNs) to lead system improvement together. It identifies programme impact at micro and meso system levels; a leadership impact continuum that can be used by individuals and teams to evidence impact of improvements in PCN practices; the learning and development strategies that were effective and proposes implications for other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…There is evidence that practice development programmes for doctors which emphasise the use of active learning (involving support, challenge, and reflection) enables selftransformation (18). Similarly, evidence ( found that supporting leaders to explore their own journey, identity and impact on teams and service was crucial in developing leadership impact, concluding that 'change starts with me' (21). As such, leaders need to find space to tell and explore their own story as a catalyst for self-discovery.…”
Section: Relations With Selfmentioning
confidence: 99%
“…There is evidence that practice development programmes for doctors which emphasise the use of active learning (involving support, challenge, and reflection) enables selftransformation (18). Similarly, evidence ( found that supporting leaders to explore their own journey, identity and impact on teams and service was crucial in developing leadership impact, concluding that 'change starts with me' (21). As such, leaders need to find space to tell and explore their own story as a catalyst for self-discovery.…”
Section: Relations With Selfmentioning
confidence: 99%
“…Apart from ICPs as IPAC specialists, there is also recognition that responsibility for IPAC should be shared by all staff working in health and social care (Sunley et al , 2017). This recognises a “continuum” of leadership agency and impact, from each individual health worker, rather than ascribing leadership only to those in senior or management positions (Jackson et al , 2021). For instance, “link nurse” roles represent a model of shared or collective IPAC leadership among clinical staff who might not necessarily have roles as ICPs.…”
Section: Background/introductionmentioning
confidence: 99%
“…In many ways, the COVID-19 pandemic has accelerated and exemplified the importance of collaboration across (and beyond) the health system, supported by staff skilled in shared and collective forms of leadership (Anjara et al , 2021). Jackson et al (2021) describe the value of relational approaches to leadership that promote shared values and purpose, that enable connection across boundaries and support compassionate cultures (Jackson et al , 2021).…”
Section: Background/introductionmentioning
confidence: 99%